2020
DOI: 10.20944/preprints202011.0662.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seven Years Maintenance Cost of Implant-Retained Overdentures on Ball Versus Locator ® Abutments.

Abstract: Denture wearers often complain about jeopardized function and reduced quality of life due to lack of prosthesis’ retention. Implant retained mandibular overdentures, on 2 non-connected implants (2IOD) are well-proven solutions to overcome these issues. We prospectively assessed 69 patients and scrutinized clinical records until at least 7 years of function. Thirty-six were retained on Locator ® Abutments (LA) and thirty-tree on Ball Abutments (BA). Both systems were compared regarding the typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The form of the NiTi element The use of prefabricated attachment systems such as locators (Zest Dental Solutions, Carlsbad, CA, USA), instead of utilizing individually fabricated attachments such as telescopic crowns or bars, drastically reduces the initial treatment costs in the edentulous mandible [13,14]. Several studies have shown that maintenance frequency [15] and associated costs [16] in such restorations are quite high, equaling or even exceeding initial treatment fees [14,17]. In particular, loss of retention and fractures of the prostheses in the area of the attachment constitute the two main technical complications [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The form of the NiTi element The use of prefabricated attachment systems such as locators (Zest Dental Solutions, Carlsbad, CA, USA), instead of utilizing individually fabricated attachments such as telescopic crowns or bars, drastically reduces the initial treatment costs in the edentulous mandible [13,14]. Several studies have shown that maintenance frequency [15] and associated costs [16] in such restorations are quite high, equaling or even exceeding initial treatment fees [14,17]. In particular, loss of retention and fractures of the prostheses in the area of the attachment constitute the two main technical complications [18,19].…”
Section: Introductionmentioning
confidence: 99%